The Effects of Hemoadsorption on the Kinetics of Antibacterial and Antifungal Agents - Giorgio Berlot; Stefano Di Bella; Ariella Tomasini; Erik Roman-Pognuz (MDPI AG, 2022)
The extracorporeal elimination of a pathogen or damage-associated molecular pattern via blood purification techniques is increasingly being used in patients with septic shock and other clinical conditions characterized by a life-threatening inflammatory response. The removal of these substances can be accomoplished by means of ultrafiltration or hemoadsorption. Independently from the blood putification technique used, they could also affect the clearance of antibacterial and antifungal agents with a potentially significant clinical impact. In our review, we describe the basic principles of ultrafiltration and hemoadsorption, the available devices for this latter and the existing experimental and clinical studies; the final paragraph is dedicated to practical considerations that can help clinicians to consider the clearance of antibiotics and antifungals attributable to these techniques to minimize the risk of a iatrogenic underdosage.